A continuous damage model of Q690D steel considering the influence of Lode parameter and its application. (30th November 2020) - Huang, Xuewei; Ge, Jianzhou; Zhao, Jun; Zhao, Wei
Highlights: A continuum damage model considering the effect of lode parameter was presented. Monotonic loading tests were conducted on different state conditions of Q690D high strength steel. Constitutive model of Q690D steel considering the influence of lode parameter were determined. Damage parameters of Q690D steel were calibrated according to experimental and numerical results. Fracture behavior of specimen with initial flaw was predicted. Abstract: Chinese Q690D high strength steel has begun to be applied in building structures in recent years, but researches on ductile fracture behavior of Q690D steel are still insufficient, and most of the mechanical fracture models based on micro fracture mechanics mechanism ignore shear effect. In this paper, the yield surface size of materials considered the shear effect through Lode parameter, and a continuous damage model (LCDM) was also provided to consider the effect of Lode parameter. A batch of Chinese Q690D high strength steel round rods and plate shaped specimens were designed to reflect different stress states, which were submitted to monotonic tensile loading. The micro fracture mechanism under different stress states was revealed by scanning electron microscopy tests. According to experimental results and finite element simulation results, LCDM parameters of Q690D steel were calibrated and crack initiation positions of various specimens were analyzed. Finally, the LCDM was used to predict crack initiation and fracture failure process of the cruciform joint specimen with initial gap. It is found that the load displacement curve, crack initiation and evolution law obtained from finite element simulation are in good agreement with the test, and the prediction accuracy based on LCDM is higher than that based on the model without considering the effect of Lode parameter.